Berberine Regulates GPX4 to Inhibit Ferroptosis of Islet β Cells - Bao, Lei; Jin, Yixuan; Han, Jiani; Wang, Wanqiu; Qian, Lingling; Wu, Weiming (Planta Medica, 2022)
Ferroptosis, as a kind of non-apoptotic cell death, is involved in the pathogenesis of type 1 diabetes mellitus (T1DM). Islet B cells mainly produce insulin that is used to treat diabetes. Berberine (BBR) can ameliorate type 2 diabetes and insulin resistance in many ways. However, a few clues concerning the mechanism of BBR regulating ferroptosis of islet β cells in T1DM have been detected so far. We measured the effects of BBR and GPX4 on islet β cell viability and proliferation by MTT and colony formation assays. Western blot and qRT-PCR were utilized to examine GPX4 expression in islet β cells with distinct treatments. The influence of BBR and GPX4 on ferroptosis of islet β cells was investigated by evaluating the content of Fe2+ and reactive oxygen species (ROS) in cells. The mechanism of BBR targeting GPX4 to inhibit ferroptosis of islet β cells was further revealed by the rescue experiment. Our results showed that BBR and overexpression of GPX4 could notably accelerate cell viability and the proliferative abilities of islet β cells. Moreover, BBR stimulated GPX4 expression to reduce the content of Fe2+ and ROS, thereby repressing the ferroptosis of islet β cells, which functioned similarly as ferroptosis inhibitor Fer-1. In conclusion, BBR suppressed ferroptosis of islet β cells via promoting GPX4 expression, providing new insights into the mechanism of BBR for islet β cells.
Keywords: berberine; GPX4; type I diabetes mellitus; islet β cells; ferroptosis